Environnement alimentaire autour du collège de Boukombé et perception des élèves sur cet environnement - Houndolo, Melina Maureen (2023)
Presented at the International Scientific Days of Nutrition in Niger, February 2023. The food environment is recognized as having a strong influence on the eating habits of individuals. This presentation highlights key findings from a study that analyzed the food environment of Boukoumbé's main college and the college students' perceptions of it. Boukoumbé is a highly food insecure commune in Northern Benin.